Cross-Border Dynamics : Analyzing Exchange Rates’ Impact on Indian Underlying Stocks and ADRs - Garg, Himanshi; Singh, Shakti (Arthshastra Indian Journal of Economics & Research, 2025)
Purpose : The study delved into the intricate interplay between Indian stocks and American depository receipts (ADRs) and examined the impact of exchange rates as the common factor bridging these two financial realms. Employing currency fluctuations, we meticulously converted ADR prices denominated in dollars into Indian rupees. The study underscored the convertibility of stock prices, the interconnectedness of exchange rates and stock prices, the long-run association between exchange rates & dual-listed securities, and the cause-and-effect dynamics of currency fluctuations. Methodology : For the study, secondary data was gathered, and an exploratory cum empirical research design was framed. Real-time closing prices were recorded monthly from January 1, 2012, to December 31, 2023. To assess the degree of integration between cross-listed securities and exchange rates, we employed Pearson correlation and cointegration analysis, while the Wilcoxon sign rank test was applied to scrutinize the variance of both Indian stocks and their ADR prices counterparts. Findings : The study revealed a robust relationship (short as well as long run) between exchange rates and stock prices in favor of the goods market theory. The Wilcoxon signed-rank test explained the significant difference amid the cross-listed stock prices. Consequently, the study posited that the exchange rate functions as a potent and ultimate parameter, serving to connect the two economies globally. Practical Implications : The study will help future researchers in framing investment strategies and policies at the global level. It also allowed generalizing the results based on developed and emerging countries by including both depository receipts, i.e., ADRs and GDRs. Furthermore, researchers can also work on the mechanism of price discovery of two different listed securities. Originality : Unlike prior research on cross-listing of securities, the current study builds interconnection between a developing economy, i.e., India, and a developed economy, i.e., America, with a common base parameter, exchange rate.